PENGARUH PROJECT BASED LEARNING TERHADAP KEMAMPUAN ANALISIS KELISTRIKAN BODY MOBIL KONVENSIONAL DAN HASIL BELAJAR SISWA KELAS XI DI SMK TAMAN KARYA MADYA TEKNIK KEBUMEN - Wibisono Dwi Ilyas; Dwi Jatmoko; Aci Primartadi; Muhlisin Rokip; Said Ismail (STKIP Subang, 2026)
This study aims to examine: (1) the partial effect of the Project-Based Learning (PjBL) model on student learning outcomes; (2) the partial effect of students’ analytical ability on learning outcomes; (3) the simultaneous effect of PjBL and analytical ability on learning outcomes; and (4) the relationship between the PjBL model and students’ analytical ability in the conventional automotive body electrical trainer project. This research employed a quantitative method with a non-experimental ex post facto design. Subjects were all 35 Class XI TKRO students at SMK Taman Karya Madya Teknik Kebumen (total sampling). Data were collected via a PjBL implementation questionnaire, an analytical ability observation sheet, and a 25-item multiple-choice achievement test. Pearson Product Moment correlation and multiple linear regression were used for data analysis. Results showed that PjBL and analytical ability simultaneously exerted a very significant effect on learning outcomes (R² = 0.969; F = 492.514; p = 0.000). Analytically, students’ analytical ability significantly predicted learning outcomes (Beta = 0.894; p = 0.000), while the partial effect of PjBL was not significant (p = 0.554) due to severe multicollinearity (VIF = 23.935). A very strong and significant correlation existed between PjBL and analytical ability (r = 0.979; p = 0.000). PjBL implementation was rated positively by 94.3% of students, and the mean learning score was 78.63 (77.1% in good–very good category), exceeding the KKM threshold of 75.